PENGARUH PENGGUNAAN MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR OPERASI HITUNG PERKALIAN PADA SISWA KELAS IV SD NEGERI 1 JANGKA BUYA - Lena Sepia; Rahmi Wahyuni; Friantiani Safitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low learning outcomes of fourth-grade students at SD Negeri 1 Jangka Buya in multiplication operations, with only 20% achieving the minimum criterion. This study aims to determine the significant effect of the make a match learning model on students' learning outcomes. A quantitative approach with a One-Group Pretest-Posttest Design was employed, involving 20 students. Data were collected using pretest and posttest tests and observation sheets, then analyzed using descriptive and inferential statistics. The Wilcoxon Signed Rank Test was applied because the data were not normally distributed. The results showed Asymp. Sig. (2-tailed) = 0.000 < 0.05, so H₀ was rejected and Hₐ was accepted. The average score increased from 48.5 to 80, and learning completeness rose from 20% to 75%. The N-Gain analysis resulted in an average of 0.645 in the moderate category, while observation of learning implementation achieved 87.5% in the very good category. Thus, the make a match learning model has a significant positive effect on students' learning outcomes in multiplication operations.